THE DEVELOPMENT FOR THE POTENTIAL OF BESAK BESAK ECOTOURISM, TANJUNG BERINGIN VILLAGE SELATAN MERAPI SUB-DISTRICT LAHAT DISTRICT SOUTH SUMATERA PROVINCE (Sylva : Jurnal Penelitian Ilmu-Ilmu Kehutanan, 2022)
Bukit Besak Nature Tourism has a unique attraction and uniqueness so that it is able to attract tourism to come and visit, so that external factors such as the facilities provided must be able to support ecotourism activities and must also pay attention to the carrying capacity of the environment so that it becomes sustainable tourism. Therefore, the Bukit Besak natural tourism must be developed by analyzing the potential for development by conducting interviews, observations, questionnaires and documentation as well as SWOT analysis. The potential of the Bukit Besak Nature Tourism is uniqueness and natural beauty, visitors with various characteristics, have supporting facilities, have adequate accessibility, and have quite good service. The development strategy of Bukit Besak ecotourism in Tanung Beringin Village is based on a SWOT analysis, namely developing ecotourism products by utilizing natural resources, tourist and cultural attractions, unique landscapes of accommodation, tools and equipment, education and skills. In developing the Bukit Besak Nature Tourism, the strategy carried out by the Lahat Regency Tourism Office is CHSE which stands for cleanliness, health, safety and environment.